IMPACT OF RESIDUAL ELEMENTS ON QUALITY OF METAL ZINC - Natália Luptáková; Františka Pešlová; Jiří Stodola (Perner’s Contacts, 2014)
The paper is closely connected with the morphology of the raw material for the production of metallic zinc which is used in the production of ZnO by indirect pyrometallurgical processes. The input material is the key parameter in the production of high-quality zinc oxide. Currently is zinc oxide the subject of considerable interest. ZnO has attracted much attention within the scientific community as a "future material". ZnO is an essential part of the aerospace industry. For the prediction of complex production process when problematic situation may occur, the systematic analysis of the input zinc materials is needed. Undesirable phases in the feedstock can be identified through profound recognition of the source material and the nature of its microstructure. Undesirable phases in the feedstock can form (with zinc and other elements) hard and brittle compounds. The results obtained by analysis are used to minimize waste - zinc slag and to eliminate the conditions which enable the formation of the undesired product, thereby increasing the productivity of the zinc oxide production.